2006
DOI: 10.1191/0269215506cr953oa
|View full text |Cite
|
Sign up to set email alerts
|

Activities of daily living and social activities in people with multiple sclerosis in Stockholm County

Abstract: ADL and social/lifestyle activities were affected in two-thirds of people with multiple sclerosis in Stockholm. The most affected items were items that could be classified as mobility-related and physically demanding, underlining the importance of developing and using evidence-based exercise treatments and rehabilitation to increase independence in people with multiple sclerosis in Stockholm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 110 publications
7
91
0
1
Order By: Relevance
“…As far as the authors are aware, no other study has used a consensus building methodology to ascertain the prioritised exercise and physical activity practices and the reasons why pwMS engage in exercise and physical activity. Similarities in the socio-demographic profile of respondents in this study and other published MS groups relating to, female to male ratio [12][13][14]26], age range [13,14,[26][27][28], type of MS classification albeit slight differences in proportions [13,14,28,29], mean Barthel score [30] and mean quality of life score [30], suggest that these results might be comparable to other typical MS community dwelling populations.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As far as the authors are aware, no other study has used a consensus building methodology to ascertain the prioritised exercise and physical activity practices and the reasons why pwMS engage in exercise and physical activity. Similarities in the socio-demographic profile of respondents in this study and other published MS groups relating to, female to male ratio [12][13][14]26], age range [13,14,[26][27][28], type of MS classification albeit slight differences in proportions [13,14,28,29], mean Barthel score [30] and mean quality of life score [30], suggest that these results might be comparable to other typical MS community dwelling populations.…”
Section: Discussionsupporting
confidence: 60%
“…Exercise on the other hand is defined as "a subset of physical activity that is planned, structured and repetitive" [10, p.126] and aims to either improve or maintain physical fitness. Studies demonstrate that pwMS participate in a wide range of physical activity, however, research to date has rarely considered the potential utility of other physical activities which are unplanned and which could be both motivating and easy to integrate into everyday life for pwMS [11][12][13][14]. Likewise, none of the studies addressed why these activities were preferred by pwMS.…”
Section: Introductionmentioning
confidence: 94%
“…Uma das escalas mais utilizadas para avaliar o desempenho nas atividades da vida diária é a Escala de Independência em Atividades da Vida Diária (EIAVD), ou Escala de Katz 4,5,6,7,8,9,10,11 . Ela foi desenvolvida para a avaliação dos resultados de tratamentos em idosos e predizer o prognóstico nos doentes crônicos.…”
Section: Adaptação Transcultural Da Escala De Independência Em Atividunclassified
“…Transportation outside the home also figured prominently among problematic areas in that study. 5 In an Italian mail survey, home assistance and home modifications were strongly associated with disease severity. 13 Khan et al 11 reported irregular access to support and rehabilita- …”
Section: Discussionmentioning
confidence: 99%
“…Transportation outside the home also figured prominently among areas of concern. 5 An opportunity to examine health status, care needs, and unmet needs in a community sample with MS arises from a Canadian post-census survey called the Participation and Activity Limitation Survey (PALS). 6 This survey is based on a probability sample of respondents reporting health-related impairments during a national census conducted in 2006.…”
mentioning
confidence: 99%